2016
DOI: 10.1016/j.colsurfb.2014.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Amaranth proteins foaming properties: Film rheology and foam stability – Part 2

Abstract: In this work the influence of pH and ionic strength on the stability of foams prepared with amaranth protein isolate was analyzed. The behaviour observed was related to the physico-chemical and structural changes undergone by amaranth protein as a result of those treatments. The results obtained show that foams prepared at acidic pH were more stable than the corresponding to alkaline pH. At pH 2.0 the foams presented higher times and more volumes of drainage. This behaviour is consistent with the characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 29 publications
0
13
0
2
Order By: Relevance
“…High ionic strength favors amaranth protein foam formation at pH 2.0 and pH 8.0 (Bolontrade and others ). However, the obtained foams are less stable than those produced at low ionic strength (Bolontrade and others ). At low ionic strength, the protein film at the interface is thicker.…”
Section: Techno‐functional Propertiesmentioning
confidence: 68%
See 2 more Smart Citations
“…High ionic strength favors amaranth protein foam formation at pH 2.0 and pH 8.0 (Bolontrade and others ). However, the obtained foams are less stable than those produced at low ionic strength (Bolontrade and others ). At low ionic strength, the protein film at the interface is thicker.…”
Section: Techno‐functional Propertiesmentioning
confidence: 68%
“…(Partial) hydrolysis of amaranth proteins into smaller fragments improves their diffusion to the air/water interface. Amaranth protein foams are more stable at pH 2.0 than at pH 8.0, due to their interfacial protein films being more viscoelastic and flexible at the former pH (Bolontrade and others ). However, the pH at which foaming is optimal seems to be cultivar‐dependent (Shevkani and others ; Steffolani and others ).…”
Section: Techno‐functional Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study of İbanoğlu and İbanoğlu (1999), foaming stability and foaming capacity of tarhana were affected by the tarhana concentration, whipping time and processing methods. Bolontrade et al (2016) reported that the foams prepared at acidic pH were stable than the alkaline pH and also reported that soluble fractions of protein showed grater stability than the total protein. In the present study, the foaming capacity of CRT, LPT and CBT were found significantly higher than control sample (WHT).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the dynamic UHPH could improve the solubility and molecular flexibility of proteins, and reduce their interfacial tension. Therefore, casein molecules were more likely to be unfolded and adsorbed at the gas-water interface and to form a hard film at the gas-water interface, thus improving the foaming properties of casein [29] . However, when the pressure level further increased, the dynamic UHPH destroyed the equilibrium between hydrophobic/hydrophilic groups.…”
Section: Effects Of Dynamic Uhph On the Foaming Properties Of Caseinmentioning
confidence: 99%